Survivors of adult cancer – their use of primary care services and unmet needs - Khan, N (2011)
The work described in this thesis concerns the use and quality of primary care service use by people living beyond a diagnosis of breast, colorectal and prostate cancer and long-term risks associated with cancer. Firstly, the thesis provides a background for this work, with a definition of long-term survivors as those living at least five years past cancer, and the role of primary care in the care of this population. The second section describes use of the General Practice Research Database amongst a cohort of cancer survivors compared to a control population. Breast and colorectal cancer survivors consult more frequently than controls up to 10 years post-diagnosis, while prostate survivors continue to see their GP up to 3 times more for at least 15 years. Most survivors receive adequate preventative care and chronic disease monitoring, excepting mammography for long-term breast cancer survivors. Cancer survivors receive more prescriptions for pain relief, anti-depressants and erectile dysfunction, suggesting higher rates of pain, depression and sexual dysfunction. Breast cancer survivors have an elevated risk of incident heart failure, coronary artery disease and hypothyroidism, while colorectal survivors experience increased risk of dementia and diabetes. All three groups of cancer survivors had higher risks of osteoporosis and second cancers, all-cause, non-cancer and cancer mortality compared to controls. The third section describes a qualitative study of the primary care usage and unmet needs of 40 long-term survivors of breast, colorectal and prostate cancer. Most respondents did not need active GP involvement. Others had ongoing information and psychological service needs. Some felt that their GPs did not have the right expertise for cancer related issues or were too busy, while others had concerns about continuity of GP care. Overall, this thesis provides a background on how the increasing numbers of cancer survivors use and experience primary care in the UK, areas of good practice, and areas where care can be improved in the future.